Synthesis of Novel 3‐Butylphthalide Derivatives Containing Isopentenylphenol Moiety as Potential Antiplatelet Agents for the Treatment of Ischemic Stroke. Issue 1 (7th December 2022) - Yu, Qinyang; Luo, Bilan; Luo, Zhongfu; Zhong, Xu; Li, Yi; Zhang, Yi; Zhu, Gaofeng; Guo, Bing; Tang, Lei; Li, Yong; Fan, Lingling
Abstract: In order to find novel antiplatelet drugs for the treatment of ischemic stroke, a series of 3‐butylphthalide derivatives containing isopentenylphenol moiety were designed, synthesized and characterized with spectroscopic analyses. The in vitro antiplatelet activity results indicated that compound 3 better inhibited the arachidonic acid (AA) induced platelet aggregation than aspirin (ASP) and 3‐butylphthalide (NBP). Additionally, compared with precursor NBP, compound 3 possessed outstanding antithrombotic activity in the animal experiment model, which could effectively alleviate the formation of tail thrombus and carotid artery thrombus in mice. More importantly, intraperitoneal administration of compound 3 can well protected the rats against ischemia/reperfusion‐induced brain injury. Further pharmacokinetic (PK) assay indicated that compound 3 had good absorption characteristics and metabolic stability in vivo . Overall, the present research provides a new candidate compound for the treatment of ischemic stroke caused by platelet aggregation. Abstract :